Neonatal-Onset Recurrent Guillain–Barré Syndrome-Like Disease: Clues for Inherited CD59 Deficiency - Ardicli, Didem; Taskiran, Ekim Z.; Kosukcu, Can; Temucin, Cagri; Oguz, Kader K.; Haliloglu, Goknur; Alikasifoglu, Mehmet; Topaloglu, Haluk (Neuropediatrics, 2017)
Inherited CD59 deficiency is a rare autosomal recessive disorder characterized by chronic hemolysis, recurrent ischemic central nervous system strokes, and early-onset relapsing peripheral demyelinating neuropathy mimicking recurrent Guillain–Barré syndrome (GBS) or chronic inflammatory demyelinating polyneuropathy (CIDP). We report a 7-year-old girl who presented with neonatal-onset relapsing weakness accompanied by diffuse sensory-motor demyelinating peripheral polyneuropathy. She was diagnosed as having a CIDP-like disease and partially responded to immunomodulatory treatments. Cranial magnetic resonance imaging showed multiphasic brainstem and cerebellar ischemic lesions consistent with vasculopathy and chronic left middle cerebral artery infarction. Whole exome sequencing (WES) analysis revealed a frameshift deletion in CD59 (c.146delA, p.Asp49Valfs*31). Inherited CD59 deficiency should be considered in the differential diagnosis of patients with early-onset severe neurologic symptoms even without an overt hemolysis. We would like to highlight the role of WES in the diagnosis of a condition with a targeted therapy.
Keywords: neonatal onset; recurrent GBS; CD59 deficiency